Translation, cross-cultural adaptation and psychometric properties of the Arabic version of the Fremantle Knee Awareness Questionnaire in people with knee osteoarthritis. - Mohammad Madi; Hayat Hamzeh; Sumayeh Abujaber; Ibrahim Altubasi (PLoS ONE)
Background The presence of distorted body awareness that is associated with knee osteoarthritis (OA) is increasingly reported in the literature. The Fremantle Knee Awareness Questionnaire (FreKAQ) is a self-reported nine-item questionnaire developed to measure distorted awareness of the knee joint. No Arabic language version of FreKAQ is currently available. Objective The study's first aim was to cross-culturally adapt FreKAQ into the Arabic language. The second aim was to test the psychometric properties of the adapted Arabic version (FreKAQ-A). Methods The adaptation phase was conducted according to recommended guidelines for translation and cultural adaptation of self-reported outcome measures. The second phase of the study evaluated the internal consistency, test-retest reliability, and validity of FreKAQ-A. Cronbach's alpha and Intraclass Correlation Coefficient (ICC) were used to test the scales' internal consistency and test-retest reliability, respectively. Validity was tested with six pre-specified hypotheses. Pain Catastrophizing Scale (PCS), Health-related Quality of Life scales (EQ-5D), Central Sensitization Inventory (CSI), and the Chronic Pain Self-efficacy Scale (CPSS) were used. Results After successful adaptation, individuals with osteoarthritic knee pain were recruited. A total of 197 individuals (19.7% males) completed the first round of reliability measurement. Almost 60% had pain in both knees. FreKAQ-A showed excellent degree of internal consistency (Cronbach's α = 0.87). The data provided strong support to five out of the six pre-specified discriminative validity hypotheses. There was a strong correlation between FreKAQ-A and PCS (rho = 0.71) and EQ-5D-5L (rho = 0.62). Seventy individuals participated in the second round of reliability measurement. Intraclass correlation coefficient was excellent (ICC2,1 = 0.841). Conclusion The study provides the first Arabic adaptation of FreKAQ. The adapted version has excellent reliability and validity. It can be used for individuals with knee osteoarthritis to explore the presence of distorted body awareness, leading to tailored management in cases with persistent knee pain.